Some strategies for the stabilization of long chain n‐3 PUFA‐enriched foods: A review. Issue 11 (29th September 2015) - Jacobsen, Charlotte
Abstract : Oil‐in‐water (o/w) and water‐in‐oil (w/o) emulsions are important colloid structures in food products, as many foods exist as emulsions. O/w emulsions, such as milk, mayonnaise, and salad dressing constitute a particularly large—and widely consumed—group of such complex, heterophasic food systems. Lipid oxidation is one of the major quality deteriorating problems in such foods. This is due to the fact that lipid oxidation is an interfacial phenomenon and since emulsions have a large interfacial area they are particularly susceptible to oxidation. Lipid oxidation is induced by transition metals, light, temperature, oxygen, and is also affected by pH, droplet size, and numerous other factors related to the composition of the emulsion. During the last decade, marine polyunsaturated n‐3 polyunsaturated fatty acids (PUFA) have increasingly been incorporated into emulsified foods in order to address recent nutritional recommendations. The increased use of n‐3 PUFA has resulted in new challenges for the food industry with respect to avoiding lipid oxidation. This review provides an overview of results obtained primarily in the author's own lab on the use of the following different strategies to reduce or inhibit lipid oxidation by: (1) optimizing the processing conditions; (2) utilizing n‐3 PUFA delivery systems; and (3) addition of antioxidants. Practical applications: This review provides an overview of how food producers can inhibit or reduce lipid oxidation in various real foods enriched with n‐3 PUFA. Particular emphasis are not only on emulsified foods, such as mayonnaise, dressing, milk, and yoghurt drink, but solid foods, such as energy bars, fish paté, and cakes are also touched upon. For emulsified foods, it is possible to reduce lipid oxidation by optimizing homogenization conditions (pressure and temperature) and the type of homogenization equipment can also affect lipid oxidation. The use of fish‐oil‐in water emulsions as an n‐3 PUFA delivery system can reduce lipid oxidation in some cases, but the delivery system must be optimized for the food system in question. Finally, lipid oxidation can also be reduced by antioxidants. The review suggests that multi‐component antioxidants with multi‐function properties in many cases may provide better efficacy than mono‐compound antioxidants. Lipid oxidation of n‐3 PUFA enriched food emulsions leads to formation of undesirable off‐flavors. Possible stabilization strategies include: Optimization of homogenization conditions, use of n‐3 PUFA delivery emulsions or antioxidant addition. Efficacy of antioxidants can be improved by designing antioxidants with the optimal molecular structure. Abstract : Lipid oxidation of n‐3 PUFA enriched food emulsions leads to formation of undesirable off‐flavors. Possible stabilization strategies include: Optimization of homogenization conditions, use of n‐3 PUFA delivery emulsions or antioxidant addition. Efficacy of antioxidants can be improved by designing antioxidants with the optimal molecular structure.